Assessing the pharmaceutical care provision to suspected COVID-19 patients in community pharmacies: a simulated patient study - Samar Karout; Hani M. J. Khojah; Rania Itani; Fatima Jaffal; Abdalla El-Lakany (BMC, 2022)
Abstract Background In the wake of COVID-19, community pharmacists (CP) were called upon to free up healthcare providers to treat more serious conditions and alleviate overcrowded healthcare centers. CPs were placed under tremendous pressure, where many patients primarily sought their health advice. This situation raised concerns about the preparedness of CPs in facing these challenges. Therefore, this study aimed to assess the appropriateness of pharmaceutical care provided by CPs to patients with suspected COVID-19 and to investigate their communication skills. Methods A simulated patient (SP) study was conducted among randomly selected community pharmacies in Beirut, Lebanon. Each pharmacy was visited by the SP who complained of fever and loss of smell sensation. Interactions between the attending pharmacist and the suspected COVID-19 patient were documented directly after each visit in a standardized data collection form. Results More than half of the CPs (56%) did not retrieve any relevant information to assess the patient's condition. While pharmacists' responses were limited to one to two recommendations, with the majority recommending the patient to perform the PCR test (90%). Inappropriate recommendations made by the CPs included mainly the confirmation that the patient had COVID-19 without prior testing (9%), and prescribing either an antimicrobial drug (5%) or dietary supplements (20%), claiming that the latter are essential to boost the patient's immunity. As for the pharmacist-patient communication skills, the mean total score was 2.25 ± 0.79 (out of 4), displaying nonoptimal and ineffective communication. Conclusion An unsatisfactory and suboptimal provision of pharmaceutical care to a suspected COVID-19 case was evident. This may be a public health threat, particularly for developing countries that lack an efficient and unified healthcare system. The findings should alert health authorities to support and guide community pharmacists in assisting suspected COVID-19 patients.